KEANEKARAGAMAN JENIS IKAN FAMILI CYPRINIDAE DI SUNGAI ARIUNG KECAMATAN PUTUSSIBAU UTARA KABUPATEN KAPUAS HULU - Septian, Sy Tarmizi; Prayogo, Hari; Dirhamsyah, M (Universitas Tanjungpura, 2020)
The cyprinidae family is a true freshwater fish that dominant in Indonesian fresh waters and the main in habitant of the most population in several rivers in Kalimantan. One of river that found cyprinidae family is Ariung river in Mendalam Village, North Putussibau District, Kapuas Hulu Regency, West Kalimantan. This study aims to obtain data on the fish diversity of the cyprinidae in Ariung River. The method used in this research is survey method and direct observation in the field. Determination of sampling points with purposive sampling and followed systematically based on environmental conditions. The results showed as many as 5 observation stations found 187 individuals belonging to 15 types, among them are Barbichthys laevis, Barbodes schwanenfeldii, Cyclocheilichtys apogon, Hampala macrolepidota, Labiobarbus ocellatus, Osteochilus hasselti, Osteochilus kappenii, Osteochilus microcephalus, Osteochilus pleurotaenia, Osteochilus waandersii, Puntioplites bulu, Rasbora caudimaculata, Rasbora sp, Thynnichthys polylepis dan Thynnichthys thynnoides. Based on the results of data analysis, the dominant index of fish in the Ariung river shows low dominance. Values (C) from the five observation stations ranged from 0.135 - 0.284. The index of fish species diversity in the Ariung river shows moderate species diversity. Diversity index (H ') values for the five stations ranged from 1.322 - 2.130. Evenness index (E) values at the five stations are at 0.912 – 0.953 and a wealth index (R) at the five stations has a high wealth of R > 4.Keywords: Ariung Rivers, Cyprinidae Family, Fish Diversity